ICE adjudication procedure (1997) a user's guide and commentary - Totterdill, Brian W. (Thomas Telford, 1998)
This title provides practical guidance to the new ICE Adjudication Procedure (1997). It includes a review of the requirements of the Housing Grants and Construction Regeneration Act 1996 and their application to construction adjudication. The Procedure is reviewed in detail, with notes on each clause and guidance for practical application.